Encapsulation of light hydrophobic liquids with fine quartz sand: Property based characterization and stability in aqueous media with different salinities. (12th May 2016) - Boglaienko, Daria; Tansel, Berrin
Abstract: A novel method for capturing oil slicks in aquatic environments with granular solids was investigated. Experiments were conducted with pure hydrophobic liquids (HL) (decane, tetradecane, hexadecane, benzene, toluene, ethylbenzene, and m-xylene) representing the main groups in crude oil (alkanes and aromatics), and fine quartz sand (passing sieve no. 40 with 0.425 mm openings). The amounts of HL captured in the HL/sand globules were correlated with the properties of HLs. Positive correlations between the aggregated HL volume with density and surface tension were observed. Aggregation number ( A N ) is introduced to estimate the amount of HL aggregated with fine quartz sand (using 0.5 mL HL and 1.0 g sand; floating HL layer thickness to particle diameter ratio >4:1). Change in the aggregated HL volume over time was examined and dissolution rate constants were obtained. Benzene and toluene completely dissolved from the aggregated globules within 3–4 days after the aggregation, while the other HLs exhibited relatively small change in the globule size over time. Salinity of water did not affect the aggregation rates of HLs but slightly decreased the dissolution rate constants for some HLs. Graphical abstract: Highlights: Salinity is not a prerequisite for the globular aggregation of HLs. Aggregation number predicts amounts of aggregated HL depending on its properties. Dissolution rate constants were the highest for benzene and toluene. Salinity of water increases stability of some of HLs in the aggregated form.